2021
DOI: 10.1128/jcm.00093-21
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Burkholderia pseudomallei Core Genome Multilocus Sequence Typing Scheme To Facilitate Molecular Surveillance

Abstract: Objectives: Burkholderia pseudomallei causes the severe disease melioidosis. Whole genome-sequencing (WGS) based typing methods currently offer the highest resolution for molecular investigations of this genetically diverse pathogen. Still, its routine application in diagnostic laboratories is limited by the need for high computing power, bioinformatic skills and variable bioinformatic approaches, the latter affecting the results. We therefore aimed to establish and validate a WGS-based core genome multilocus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…However, the Burkholderia-specific MLST scheme [21] fails to differentiate the highly clonal B. mallei strains while an MLVA scheme [22] provides higher resolution, but the investigated repeat regions are prone to homoplasy. Recently, a cgMLST scheme for B. pseudomallei, the assumed progenitor of B. mallei, was proposed [32]. As this scheme could also not sufficiently differentiate B. mallei strains (unpublished data), a B. mallei-specific cgMLST scheme was developed in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the Burkholderia-specific MLST scheme [21] fails to differentiate the highly clonal B. mallei strains while an MLVA scheme [22] provides higher resolution, but the investigated repeat regions are prone to homoplasy. Recently, a cgMLST scheme for B. pseudomallei, the assumed progenitor of B. mallei, was proposed [32]. As this scheme could also not sufficiently differentiate B. mallei strains (unpublished data), a B. mallei-specific cgMLST scheme was developed in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…As in the present study, the true epidemiologic connection between isolates remained elusive, and further studies are required to determine this value for B. mallei. Such a threshold is also not known yet for B. pseudomallei cgMLST analyses, as even two alleles separate outbreak strains of a single transmission event from unrelated isolates and epidemiological connections were merely assumed for isolates differing by one allele [32]. A similarly strict differentiation could be expected for B. mallei.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a cgMLST assay has been published for B . pseudomallei recently [ 26 ], for B . mallei no cgMLST assay was available.…”
Section: Introductionmentioning
confidence: 99%
“…The only two samples which became culture-positive were collected from a grassland in Udupi and a paddy field in Shimoga during the monsoon and showed remarkably high loads by direct qPCR (Figure 5). Whole genome sequencing of those isolates and subsequent cgMLST (Lichtenegger et al, 2021) revealed clustering in the same group with other Indian isolates and strains from Sri Lanka, but also showed remarkable genetic difference between each other (Figure 9).…”
Section: Discussionmentioning
confidence: 80%
“…Illumina short reads of the environmental B. pseudomallei isolates from this study were submitted to the Sequence Read Archive under the NCBI accession ERR9146399 (IND_S3) an ERR9138530 (IND_S14). Whole genome sequencing data of B. pseudomallei strains were analyzed in SeqSphere (Ridom GmbH, Germany) using our previously published B. pseudomallei core genome MLST (cgMLST) scheme (Lichtenegger et al, 2021). A UPGMA tree and a minimum spanning tree were constructed based on the allelic profiles of the isolates.…”
Section: B Pseudomallei Phylogenetic Analysismentioning
confidence: 99%